The enemy between us: The psychological and social costs of inequality - Wilkinson, Richard G.; Pickett, Kate E. (European Journal of Social Psychology, 2017)
There is now substantial evidence that larger income differences in a society increase the prevalence of most of the health and social problems that tend to occur more frequently lower down the social ladder. The pathways through which human beings are sensitive to inequality are however less clear. This paper outlines the explanatory theory that we think best fits the growing but incomplete body of evidence available. Inequality appears to have its most fundamental effects on the quality of social relations—with implications affecting the prevalence of a number of psychopathologies. We suggest that human beings have two contrasting evolved social strategies: one that is adaptive to living in a dominance hierarchy and the other appropriate to more egalitarian societies based on reciprocity and cooperation. Although both strategies are used in all societies, we hypothesise that the balance between them changes with the extent of material inequality.
Keywords: evolutionary psychology; health; income inequality; social relations; status